CDK9 inhibitors define elongation checkpoints at both ends of RNA polymerase II-transcribed genes - Laitem, Clélia; Zaborowska, Justyna; Isa, Nur Firdaus; Kufs, Johann; Dienstbier, Martin; Murphy, Shona (Nature Publishing Group, 2015)
Transcription through early-elongation checkpoints requires phosphorylation of negative transcription elongation factors (NTEFs) by the cyclin-dependent kinase (CDK)9. Using CDK9 inhibitors and global run-on sequencing (GRO-seq), we have mapped CDK9 inhibitor-sensitive checkpoints genome-wide in human (Homo sapiens) cells. Our data indicate that early-elongation checkpoints are a general feature of RNA polymerase (pol) II-transcribed human genes and occur independently of polymerase stalling. Pol II that has negotiated the early-elongation checkpoint can elongate in the presence of inhibitors but, remarkably, terminates transcription prematurely close to the terminal polyadenylation (poly(A)) site. Our analysis has revealed a hithertounsuspected poly(A)-associated elongation checkpoint, which has major implications for the regulation of gene expression. Interestingly, the pattern of modification of the carboxyl-terminal domain (CTD) of pol II terminated at this novel checkpoint largely mirrors the pattern normally found downstream of the poly(A) site, suggesting common mechanisms of termination